1991
DOI: 10.1037/0894-4105.5.4.267
|View full text |Cite
|
Sign up to set email alerts
|

The other victims of traumatic brain injury: Consequences for family members.

Abstract: Traumatic brain injury (TBI) is both an acute and a chronic impairment, with long-term difficulties affecting both the patient and members of the patient's family. The impact of TBI may be different for spouses, parents, children, and siblings, and they can be portrayed as the other and often neglected victims of the trauma. Family members are a potentially high risk group, often requiring intensive intervention services and support, not just as caregivers but also as a treatment target population in their own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
4
30
1
Order By: Relevance
“…They ranged in age from 19 to 84 years (mean age=43.7 years). Patients had a mean Glasgow Coma Score [28] of 10.2 (range: [6][7][8][9][10][11][12][13][14], with 70% scoring in the moderate injury range (9)(10)(11)(12). Their Injury Severity Scores [29] ranged from 25.0 to 60.0 with a mean of 31.35, and a standard deviation of 8.66.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They ranged in age from 19 to 84 years (mean age=43.7 years). Patients had a mean Glasgow Coma Score [28] of 10.2 (range: [6][7][8][9][10][11][12][13][14], with 70% scoring in the moderate injury range (9)(10)(11)(12). Their Injury Severity Scores [29] ranged from 25.0 to 60.0 with a mean of 31.35, and a standard deviation of 8.66.…”
Section: Subjectsmentioning
confidence: 99%
“…Findings for families of TBI patients are not as consistent in this regard, with many studies indicating that family member psychological distress increases over time and is highest during patient recovery when family members assume the role of caregiver. A significant percentage of caregivers report experiencing clinically significant levels of emotional distress even 6 years or more after patient discharge [12][13][14][15]. This likely reflects the uncertainty and variable course of TBI recovery as the patient sometimes progresses to chronic disability and both patient and caregiver must face the challenges of reintegration into the community.…”
Section: Introductionmentioning
confidence: 95%
“…These parents may never be able to enjoy the independence they had anticipated in later life. As well, older parents who may be accustomed to an empty nest or child-free lifestyle may have to return to a parenting role that they had not been emotionally or financially prepared for (Florian & Katz, 1991;Lezak, 1988).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, many studies have suggested that TBI has strong, pervasive and long-lasting negative effects on caregivers. Indeed, stress, emotional (depression, anxiety) and psychosomatic disorders, financial difficulties, or disturbances in social and family functioning have been frequently described by the patients’ caregivers [2,3]. In particular, behavioural and emotional changes displayed by patients with TBI are better predictors of the caregiver burden than injury severity or cognitive impairments [4].…”
Section: Introductionmentioning
confidence: 99%